Unveiling Earthquake Interpretation Insights from Tetamba Cirebon Manuscript - Hidayani, Fika; Arfan, Am'mar Abdullah (IAIN Syekh Nurjati Cirebon, 2024)
This research explores the seismic interpretations of the Tetamba Cirebon manuscript, providing a comprehensive analysis of gender dynamics, spirituality, and minority perspectives in the context of seismic events. The manuscript’s emergence not only reveals seismic interpretations but also indicates a cultural shift towards inclusivity within the spiritual domain. This shift challenges established norms by advocating for a more equitable representation of both men and women in spiritual discourse. Additionally, this manuscript provides a platform for minority communities to express their unique perspectives on significant events. It is essential to acknowledge and respect the diverse narratives woven by our ancestors in this exploration. The text’s significant contribution is in providing a deep understanding of the complex relationship between spirituality and seismic phenomena. It offers new insights into how minority groups respond to and interpret these events. In addition to uncovering seismic interpretations, this research establishes a basis for promoting open and inclusive discussions about the diversity of spiritual beliefs. This research aims to encourage a broader exploration of the meaning behind earthquake interpretations, beyond their classification as seismic events. These interpretations are viewed as stories that are intricately linked to the spiritual essence of various cultures. It also broadens perspectives on seismic events by recognizing the rich tapestry of spiritual beliefs, values, and relationships interwoven in this narrative